Stability analysis of semi-trimaran flat hull ship for a sea transportation model - Putra, Gerry Liston; Wibowo, Hadi Tresno; Agusta, Fendra (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2017)
Indonesia as an archipelagic nation highly requires a model of sea transportation as interconnection mainframe between islands. An effective and efficient use of sea transportation is the main factor to improve Indonesian economy. Therefore, it is necessary to optimize the sea transportation model that services throughout Indonesian sea. It has been known that an alternative solution to this specific need is the use of Semi Trimaran Flat Hull Ship. The main supporting reason is the good stability feature owned by this ship design. The focal point of this research is to evaluate the stability test using inclining method according to international standard. Maximum righting lever (GZ) obtained is 4.59 cm for the model size or 1.377 m for the original size in 57.3 degrees. The value is greater than 25 degrees as a standard value. Thus, the result of ship stability analysis shows that semi-trimaran Flat Hull Ship has complied with all IMO (International Maritime Organization) criteria. All of these results indicate that this ship has good stability feature and fit to be continued in a physical testing.